ChemInform Abstract: Development of a Direct Photocatalytic C—H Fluorination for the Preparative Synthesis of Odanacatib. Issue 13 (March 2016) - Halperin, Shira D.; Kwon, Daniel; Holmes, Michael; Regalado, Erik L.; Campeau, Louis‐Charles; DiRocco, Daniel A.; Britton, Robert
Abstract: A one‐step photocatalytic fluorination of (S)‐leucine methyl ester (I) is thoroughly elaborated which allows for the multi‐gram preparation of (S)‐γ‐fluoroleucine methyl ester (II) under continuous flow conditions, thus representing a straightforward access to the critical intermediate (II) of odanacatib (III).